Gambaran Persepsi Dukungan Organisasi terhadap Kesehatan dan Keselamatan Kerja (K3) Karyawan di Perusahaan Logistik CV WPA - Winny Angelica Wiweko; Benedicta Prihatin Dwi Riyanti (Fakultas Psikologi Universitas Pancasila, 2023)
Occupational Health and Safety (K3) of Employees has become the rights and obligations that must be fulfilled by the company to its Employees. In this context, Perceived Organizational Support, otherwise known as (POS), is an important factor that can give Employees a sense of value and encourage their positive contribution to the company. This study aims to identify a description of the perceptions of Employee Organizational Support at the logistics company CV WPA. The method used in this research is quantitative with a descriptive study approach. This study also involved a differential test to identify differences in the dimensions of Perceived Organizational Support based on factors such as age, gender, education, length of service, and Employee position. The results of the study show that the POS level is quite good, although there are still some Employees who perceive the POS level at CV WPA as lacking. The results also show that there are no significant differences in all POS dimensions. Tests for differences in age, education and length of work also did not show significant differences related to POS, while there were significant differences related to POS based on gender and position.